Identifying Students’ Intrinsic and Extrinsic Motivation in Online Learning Amidst Pandemic COVID-19 - Prakoso, Kholufah Catur; Wijaputra, Bambang Arya; Fitriyah, Siti Masrifatul (EFL Education Journal, 2022)
this research was intended to find out the students’ intrinsic and extrinsic motivation in online learning amidst pandemic Covid-19. The research design was surveys with the research participant were the eleventh-grade students. The result of the questionnaires showed that the eleventh-grade students have very strong extrinsic motivation rather than intrinsic motivation in online learning. The students need a comfortable atmosphere in teaching and learning process. Besides, the students motivate to learn English because they want to get good score, they want to continuing their study and also to get compliment from their parents.